Could "triple-therapy" considered as a novel-optimal treatment model for acute bipolar depression? A prospective real-world research in China. (December 2020) - Zhou, Yaling; Zhang, Xu; A., Ruhan; Chen, Yuexin; Sun, Xueli
Abstract: Background: Results of researches of bipolar depression treatment are inconsistent and to our knowledge, no study has previously revealed an optimal treatment model for bipolar depression in the real-world through a prospective way. Objective: To find out an optimal treatment model for bipolar depression in the real-world by evaluating the effect of different treatment models: monotherapy, double-therapy and triple-therapy. Design: and Intervention: This 12 or 16-week, multi-center, real-world clinical study was conducted at 15 study sites (inpatient or outpatient department) in West China and a total of 573 patients completed the follow-up. During the study weeks, all researchers could choose a most proper treatment model freely basing on the evaluation of patient's symptoms and complete the follow-up according to the procedure. Main outcomes and measures: The primary outcomes were baseline-to–endpoint change in Montgomery-Asberg Depression Rating Scale (MADRS) total score and the constituent ratio of effects. Total score change in Young Mania Rating Scale (YMRS) and Clinical Global Impression (CGI) from baseline to endpoint, treatment-emergent mania rate and severe adverse events rate were used as secondary outcomes. Results: During all study weeks, all the 3 groups showed a statistically significant improvement in MARDS, YMRS and CGI ( P ＜0.001), but the triple-therapy group showed much more effective in significant response and response rates at endpoint than double-therapy group and monotherapy group ( P ＜0.001) with lower treatment-emergent mania rates ( P  = 0.001). At week 4, mean scores of MARDS in triple-therapy group are statistically significant lower than monotherapy group ( P  = 0.013) and at the endpoint, mean scores of MARDS in triple-therapy group are statistically significant lower than both double-therapy and monotherapy groups ( P  = 0.011). The severe adverse events rates are rare in all the 3 groups at week 4 and endpoint, and the rate of dry mouth in triple-therapy group at week 4 is statistically significant lower than the other 2 groups ( P  = 0.002). Conclusions: Triple-therapy is more effective in treating bipolar depression than double-therapy and monotherapy model with a lower risk of developing manic symptoms. Trial registration: Chinese Clinical Trial Registry. Identifier: ChiCTR1800019064.